Effect of Overground Walking and Treadmill Exercise on Walking Speed and Walking Ability in Elderly - Novy, Theresia Chandra Tania; Vitriana, Vitriana; Sastradimaja, Sunaryo Barki; Defi, Irma Ruslina (Faculty of Medicine Universitas Padjadjaran, 2013)
Objective: To compare the effect of overground walking and treadmill exercise on walking speed and ability in elderly from week to week. Methods: This study was conducted in 6 weeks to 18 elderly at Panti Wreda Karitas and Nazareth Bandung (September–December 2011). They were divided into two groups; overground walking exercise group and treadmill group. Walking speed and ability was measured using 10 meter walk test and 6 minute walk test consecutively. Results: Both group walking speed was improved after 1 and 2 weeks exercise (p=0.019 and p=0.050), consecutively. Walking ability in the overground and treadmill group was improved after 1 and 3 weeks exercise (p=0.019 and p=0.009), consecutively. Overground walking group showed greater improvement in walking speed and ability after 3 weeks exercise (p=0.008 and p=0.017) consecutively. Conclusions: Three weeks overground walking exercise improves walking speed and ability better than treadmill exercise. Keywords: Elderly, overground walking exercise, treadmill exercise, walking ability, walking speed DOI: 10.15850/ijihs.v1n1.105